2018
DOI: 10.3899/jrheum.170896
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Arterial and Venous Thrombosis in Antineutrophil Cytoplasmic Antibody–associated Vasculitis

Abstract: Objective.To determine the incidence of arterial thrombotic events (ATE) and venous thromboembolism (VTE) in antineutrophil cytoplasmic antibody–associated vasculitis (AAV).Methods.This is a retrospective cohort study presenting the incidence of ATE (coronary events or ischemic stroke) and VTE [pulmonary embolism (PE) or deep venous thrombosis (DVT)] in patients diagnosed with AAV between 2005 and 2014.Results.There were 204 patients with AAV who were identified. Median followup for surviving patients was 5.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 31 publications
5
26
0
2
Order By: Relevance
“…A long-term population-based study revealed that the risk of CVD and CVA in AAV patients were 3-and 8-fold higher than those in matched subjects [22]. In addition, a retrospective study that was performed in the United Kingdom has shown that AAV patients have high incidence of arterial and venous thrombosis [23]. Moreover, a meta-analysis by Houben et al demonstrated that the risk of developing cardiovascular events was higher in AAV patients compared to the general population [24].…”
Section: Discussionmentioning
confidence: 99%
“…A long-term population-based study revealed that the risk of CVD and CVA in AAV patients were 3-and 8-fold higher than those in matched subjects [22]. In addition, a retrospective study that was performed in the United Kingdom has shown that AAV patients have high incidence of arterial and venous thrombosis [23]. Moreover, a meta-analysis by Houben et al demonstrated that the risk of developing cardiovascular events was higher in AAV patients compared to the general population [24].…”
Section: Discussionmentioning
confidence: 99%
“…Venous thromboembolism (VTE) is a classical complication of chronic inflammatory diseases [ 1 ], reported to be increased in many auto-immune and rheumatic diseases, including ANCA-associated vasculitis (AAV) [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. The first studies specifically addressed in AAV were a case series of pediatric patients that developed deep vein thrombosis (DVT) shortly after disease diagnosis [ 10 ] and a post-hoc analysis of the Wegener’s Granulomatosis Etanercept Trial (WGET) [ 2 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A long-term populationbased study revealed that the risk of CVD and CVA in AAV patients were 3-and 8-fold higher than those in matched subjects [22]. In addition, a retrospective study that was performed in the United Kingdom has shown that AAV patients have high incidence of arterial and venous thrombosis [23]. Moreover, a meta-analysis by Houben et al demonstrated that the risk of developing cardiovascular events was higher in AAV patients compared to the general population [24].…”
Section: Discussionmentioning
confidence: 99%